Vegetation and slopes stabilisation, protection and ecology : proceedings of the international conference held at the University Museum, Oxford 29-30 September 1994 - Barker, D. H. (Thomas Telford, 1995)
Co-sponsored by the British Geotechnical Society, the Institute of Terrestrial Ecology and the Oxford Forestry Institute, this work will be of practical benefit to engineers, clients designers, managers and researchers in vegetation science.